Zooplankton-Mediated Fluxes in the Eastern Tropical North Atlantic - Kiko, Rainer; Brandt, Peter; Christiansen, Svenja; Faustmann, Jannik; Kriest, Iris; Rodrigues, Elizandro; Schütte, Florian; Hauss, Helena (Frontiers in Marine Science, 2020)
Zooplankton organisms are a central part of pelagic ecosystems. They feed on all kinds of particulate matter and their egested fecal pellets contribute substantially to the passive sinking flux to depth. Some zooplankton species also conduct diel vertical migrations (DVMs) between the surface layer (where they feed at nighttime) and midwater depth (where they hide at daytime from predation). These DVMs cause the active export of organic and inorganic matter from the surface layer as zooplankton organisms excrete, defecate, respire, die and are preyed upon at depth. In the Eastern Tropical North Atlantic (ETNA), the daytime distribution depth of many migrators (300-600 m) coincides with an expanding and intensifying oxygen minimum zone (OMZ). We here assess the day and night-time biomass distribution of mesozooplankton with an equivalent spherical diameter of 0.39 to 20 mm in three regions of the ETNA, calculate the DVM-mediated fluxes and compare these to particulate matter fluxes and other biogeochemical processes. Integrated mesozooplankton biomass in the ETNA region is about twice as high at a central OMZ location (cOMZ; 11\si{°} N, 21\si{°} W) compared to the Cape Verde Ocean Observatory (CVOO; 17.6\si{°} N, 24.3\si{°} W) and an oligotrophic location at 5\si{°} N, 23\si{°} W (5N). At cOMZ, an in comparison to the other regions particularly strong Intermediate Particle Maximum (IPM) is found, which seems to be related to DVM activity. Zooplankton DVM is responsible for about 29 to 42% of nitrogen loss from the upper 200m of the water column. Gut flux and mortality make up about \ivall{Perc_DVM_O2_flux_into_OMZ-cOMZ}% of particulate matter supply to the 300 to 600 m depth layer at cOMZ, whereas it makes up about \ivall{Perc_DVM_O2_flux_into_OMZ-CVOO}% and \ivall{Perc_DVM_O2_flux_into_OMZ-5N}% at CVOO and 5N, respectively. Resident and migrant zooplankton are responsible for about 6 to 23% of the total oxygen demand at 300 to 600 m depth. Changes in zooplankton abundance and migration behavior due to decreasing oxygen levels at midwater depth could therefore alter the elemental cycling of oxygen and carbon in the ETNA OMZ and impact the removal of nitrogen from the surface layer.